Fatores que influenciam na permanência de médicos na Atenção Primária à Saúde após conclusão da residência de medicina de família e comunidade no Estado da Paraíba - Oliveira, José Danúzio Leite de (2024)
In the last decade, there has been a 250% increase in the number of doctors trained in Family and Community Medicine (FCM) residency programs in Brazil; however, it is estimated that there is a demand for training around 50,000 specialists to work in Primary Health Care (PHC) teams, especially in more remote regions with vulnerable populations. This study investigates the factors associated with the intention of doctors linked to the ten FCM residency programs in the state of Paraíba to continue working in PHC. This is a cross-sectional, analytical study with a quantitative approach and a census-type sample of 211 doctors, residents and preceptors. Data was obtained using an electronic questionnaire administered in the second half of 2023. Descriptive, bivariate (Chi-square and Fisher's exact) and logistic regression analyses were carried out. The grouping variable “intention to continue working in PHC” was found to be associated with sociodemographic and academic variables and intrinsic and extrinsic factors that could influence doctors' decisions. The majority were female (61.6%), without a partner (57.3%), and without children (82%). 42 (19.9%) worked as preceptors and 169 (80.1%) as residents. 90.5% of the preceptors intended to continue in primary care, compared to 54.4% of the residents. There was an association between being married or in a stable union (p=0.031), having children (p=0.002), having graduated from a public institution (p=0.017) and experience in Primary Care (p=0.049) with the grouping variable. Most doctors make this decision during their undergraduate studies (p<0.001), the period of experience in PHC contributes to the decision (p=0.002), as do more stable employment relationships, such as permanent (p=0.015), statutory (p<0.001), the offer of a master's degree (p<0.001). The intention of doctors linked to the ten FCM residency programs in the state of Paraíba to continue working in PHC is associated with their identification with the area. The decision is made during graduation and strengthens with experience. More stable employment relationships, the offer of a master's degree in the area and the opportunity to act as a preceptor in the FCM residency program all contribute to the desire to remain in PHC throughout their professional career. The technical product produced consisted of a conclusive technical report, in the form of a portfolio for dissemination, summarising the findings of the research group's work, as well as suggestions and recommendations for the study participants, with a view to improving the training process implemented in the residencies. This master’s degree final paper is the result of the Professional Master's Degree in Family Health (PROFSAÚDE) stricto sensu postgraduate programme.